A scientometric assessment of research productivity on Child Maltreatment from Web of Science database - Dinakaran Munnu; Gomathi Palanisamy (Encontros Bibli)
Objective: This study examines the research productivity on child maltreatment across the globe from 2012 to 2021. Furthermore, we employed scientometric statistic measurements to analysis of child maltreatment productivity.